Evaluating the Acceptance of Blockchain Technology in the Supply Chain of Lombok Traditional Weaving Industry Using Extended Technology Acceptance Model - Kurrotaa'yun, Baiq Dwi Zulianti; Wijayanto, Heri; Widiartha, Ida Bagus Ketut; Afwani, Royana; Agitha, Nadiyasari; Murpratiwi, Santi Ika (Prodi Pendidikan Teknik Informatika Universitas Pendidikan Ganesha, 2025)
Traditional Sasak weaving in Lombok faces major challenges such as counterfeit products, lack of supply chain transparency, and price disparities, all of which undermine sustainability and consumer trust. Blockchain technology offers potential solutions by improving transparency, security, and data integrity. However, adoption among weaving MSMEs (Micro, Small, and Medium Enterprises) remains limited due to low digital literacy and limited awareness of blockchain’s benefits. This study evaluates the acceptance of blockchain technology among traditional weaving MSMEs in Lombok using an Extended Technology Acceptance Model (TAM). Beyond the standard constructs Perceived Usefulness (PU) and Perceived Ease of Use (PEU) the model integrates Perceived Trust (PT), Perceived Privacy (PP), Perceived Security (PS), Social Influence (SI), and Customer Satisfaction (CS). A quantitative survey was conducted with 50 MSME actors in Sukarara, Lombok. Findings show that PEU significantly influences PU (path coefficient = 0.798; t = 11.520; p < 0.001), while Attitude Toward Using (ATU) strongly affects Behavioral Intention to Use (BITU) (path coefficient = 0.775; t = 5.147; p < 0.001). Both PS and PP significantly impact PT, with path coefficients of 0.410 and 0.380, respectively. Conversely, SI and CS have no significant effect on BITU. The model demonstrates strong explanatory power, with R² values of 81.7% for ATU and 80.7% for BITU. These results highlight that technical factors particularly usability and trust are more influential than social factors in determining blockchain adoption. The study recommends simplifying technology, improving digital literacy, and ensuring policy support to drive wider adoption among traditional MSMEs.